Reproductive biology and ecological strategies of three species of medicinal leeches (genus Hirudo) - Petrauskienė, Laima; Utevska, Olga; Utevsky, Serge (Journal of natural history, 2011)
An analysis of the reproduction of three species of medicinal leeches (genus Hirudo) was carried out. The highest fecundity (34.34 ± 3.72 hatchlings per leech) was observed in H. verbana, the lowest in H. medicinalis (11.10 ± 2.56). The heaviest hatchlings were found in H. medicinalis (0.046 ± 0.0005 g), the lightest in H. verbana (0.032 ± 0.0003 g). Hirudo orientalis had an intermediate fecundity (21.63 ± 3.39 hatchlings per leech) and its hatchlings were of intermediate weight (0.038 ± 0.0005 g). The species differ in their growth rate and mortality: Hirudo verbana had the smallest hatchlings and the lowest survivorship but its growth rate was highest among the three species. The results agree with sister relationships between H. medicinalis and H. orientalis and the basal position of H. verbana with respect to them. The reproductive traits of the three species suggest that H. verbana is an r-strategist that inhabits unstable environments, such as temporary ponds in steppe landscapes, whereas its congeners are subject to K-selection and occur in more stable and predictable habitats.